2016
DOI: 10.7600/jpfsm.5.349
|View full text |Cite
|
Sign up to set email alerts
|

Interlimb coordination from a psychological perspective

Abstract: During coordination of the movement of two limbs, the movements often interfere with each other, i.e., interlimb coordination is constrained. Many movement-related parameters such as movement direction, movement frequency, the coupling of limbs, neural network among limbs, and muscle homology are considered constraints of interlimb coordination, and they are roughly consolidated into two constraints, a neuromuscular constraint, and a perceptual-cognitive constraint. Interlimb coordination is considered to be g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 154 publications
0
5
0
Order By: Relevance
“…However, practice of complex multi-limb movements using motor imagery may not overcome the constraint of interlimb coordination, because our results suggested that there is a strong constraint during motor imagery of multi-limb coordination with the neural circuits facilitating the directional constraint. To overcome the constraint during motor imagery, we may need to adjust the imagery so as to avoid making imagery of each limb movement but making them as one integrated movement, as previous studies showed non-perception of each limb movements can overcome the interlimb constraint during actual movements (Mechsner et al, 2001;Kovacs et al, 2010;Muraoka et al, 2016). Therefore, the present study provided important suggestion on the application of practice or learning using motor imagery.…”
Section: Clinical Significancementioning
confidence: 86%
“…However, practice of complex multi-limb movements using motor imagery may not overcome the constraint of interlimb coordination, because our results suggested that there is a strong constraint during motor imagery of multi-limb coordination with the neural circuits facilitating the directional constraint. To overcome the constraint during motor imagery, we may need to adjust the imagery so as to avoid making imagery of each limb movement but making them as one integrated movement, as previous studies showed non-perception of each limb movements can overcome the interlimb constraint during actual movements (Mechsner et al, 2001;Kovacs et al, 2010;Muraoka et al, 2016). Therefore, the present study provided important suggestion on the application of practice or learning using motor imagery.…”
Section: Clinical Significancementioning
confidence: 86%
“…For a target article on Mechsner's research with commentaries, see Mechsner (2004aMechsner ( , 2004b. See also Muraoka et al (2016), for a thorough refutation of common criticisms of Mechsner's ideas. See Abrahamson (2019) for an overview of his research.…”
Section: Mechsner Et Al's (2001) Conclusionmentioning
confidence: 99%
“…The coordination of multi-limb movement involving both contraction and relaxation is quite complicated and is known to be “not just a simple addition of activities of muscle in different limbs and the other’s activity” (Swinnen, 2002). For example, when performing repetitive cyclic movements of both hands or ipsilateral limbs, the movements interfere with each other (Remote effect; Kelso et al, 1979; Nakagawa et al, 2015; Muraoka et al, 2016). During the cyclic movement of ankle dorsiflexion and planterflexion, the corticospinal excitability of resting ipsilateral muscles in the forearm (flexor and extensor muscles) changes depending on the phase of ankle movement.…”
Section: Coordination Of Multi-limb Muscles Underlying Relaxationmentioning
confidence: 99%
“…Compared with the motor control system involved with simple muscle relaxation, control of muscle relaxation during multi-limb coordination is poorly understood. Although numerous studies have demonstrated that muscle contraction of one limb interferes with muscle activity in the other limbs (“remote effect”; Baldissera et al, 1998; Swinnen, 2002; Muraoka et al, 2016; Zheng et al, 2018), the behavioral and neural mechanisms involved in this “remote effect” of muscle relaxation are not well understood.…”
Section: Introductionmentioning
confidence: 99%